Overview of Sport-Specific Injuries. Issue 4 (December 2021) - Scanaliato, John P.; Wells, Matthew E.; Dunn, John C.; Garcia, E'Stephan J.
Abstract : Athletes are at risk for a variety of injuries not typically sustained in everyday life. The team physician must be capable of not only identifying and treating injuries as they occur, but he or she must be armed with the knowledge to minimize the risk of injuries before they occur. This review serves to provide an overview of the various sport-specific injuries typically encountered by team physicians. Injuries are grouped by body part and/or organ system, when possible. We do not aim to cover in detail the various treatments for these injuries; rather, we hope that this article provides a comprehensive overview of sport-specific injury, and demonstrate the well-roundedness in skills that must be possessed by team physicians.